A new technique for repairing reinforced concrete columns. (July 2020) - Obaidat, Yasmeen Taleb; Ashteyat, Ahmed M.; Obaidat, Ala' Taleb; Alfaris, Suhaib F.
Abstract: Experimental work was conducted to investigate the behavior of repaired and strengthened reinforced concrete (RC) rectangular columns by flexible near surface mounted –carbon fiber reinforced polymer (NSM-CFRP) cord. Thirteen RC column specimens were tested under axial load. Eight specimens were preloaded up to 70% of the maximum axial load and repaired using NSM-CFRP cord with different configurations, spacing, anchoring location, and groove size while the last one was repaired using CFRP sheet. Test results showed that the NSM CFRP cord technique is more efficient in increasing compressive strength than CFRP sheet. Repairing RC columns with NSM CFRP cords provided up to 171% increase in axial load capacity, while repairing with fully two layers of CFRP sheet provided up to 138% increase in axial load capacity, compared to the control columns. The study showed that significant gains in axial strength can be achieved by using larger width to depth ratio and smaller spacing between CFRP cords. Also a modified design model to predict the capacity of repaired columns using NSM-CFRP cord was proposed. Accuracy of the proposed model was checked against the test results. Capacity prediction using the proposed model showed good agreement with the experimentally strengthened or repaired columns, which means the modified design model is capable of predicting the load of NSM-CFRP cord columns. Highlights: Experimental works were conducted to examine the effect of using NSM-CFRP cord. NSM CFRP cord technique is more efficient in increasing compressive strength. A modified design model was proposed.